BATIK AS THE CRYSTALLIZATION OF CULTURAL ELEMENTS - Dian Andi Suleman (Universitas Sebelas Maret, 2017)
Batik is a classic art work that is owned by the Indonesian. As a work containing the noble values of the nation, batik was created from the crystallization of the visualized culture and in the knowledge of batik both in ideas, behavior and form. The purpose of this study is to describe the existence of batik as a work of art of the nation in terms of elements of cultural elements formed from the batik .. This research uses descriptive qualitative methods, with literature review and interview informants. Based on the study and analysis of the literature and field data, it was concluded that in culture all elements of a culture full of values have a role in the ideology, behavior and form/artefact of batik itself then batik is a work that becomes a crystallization of how reality in the culture of the owner which is very sublime. So batik is an art filled with cultural values, works that have meaningful symbols and art that reflect the identity of his nationality. So it can be concluded that batik as a result of Indonesian culture is a high quality work and transformed into a commodity identity of the nation.